Application of VVI layered strain technology to analyze changes in left ventricular myocardial motion in patients with uremia - Xinyan Dai; Yihua Gao; Xianglan Fang; Hailan Zheng (PLoS ONE, 2026)
Objective Velocity vector imaging (VVI) stratified strain analysis was used to assess circumferential strain across myocardial layers in uremic patients using a 16-segment left ventricular model. Methods Data were accessed for research purposes from 1/5/2025–1/6/2025. Sixty hemodialysis patients were divided into left ventricular hypertrophy (LVH, n = 30) and normal LV conformation (LVN, n = 30) groups based on LV mass index, alongside 27 healthy controls (CON). Clinical and echocardiographic data were analyzed, with VVI quantifying systolic circumferential strain (CS) in endocardial (Endo), mid-myocardial (Myo), and epicardial (Epi) layers. Results The LVH and LVN groups exhibited significant differences compared to the CON group in SBP, Hb, BUN, Scr, eGFR, and hsCRP levels ( P < 0.001). Hb levels were uniquely reduced in LVH versus LVN ( P < 0.05). Both uremic groups had larger cardiac dimensions (LAD, LVPTW, IVST, LVIDd, LVIDs) than CON ( P < 0.001), but similar LVEF ( P > 0.05). Basal and mid-segment global strain were impaired in LVH/LVN ( P < 0.05), while apical strain differences were only significant in the Epi layer. LVH showed reduced anteroseptal basal strain (Endo/Myo/Epi-2CS) and inferoseptal basal (Endo/Myo-3CS) and anterolateral mid (Epi-12CS) strain versus LVN. Anteroseptal (Endo/Myo/Epi-2CS) and inferoseptal (Endo/Myo-3CS) strains correlated with Hb levels ( P < 0.01). Anteroseptal basal strains (Endo/Myo/Epi-2CS) and their combined values significantly predicted myocardial remodeling (AUC, P < 0.001). While Epi-3CS and its combined values (Endo/Myo/Epi-2CS) did not ( P > 0.05). Conclusions The VVI layered strain technique is a precise and sensitive tool for evaluating LV myocardial motion in uremic patients.